Refractive index gradient in the lens: reflections on form and function and on the lens paradox - Pierscionek, Barbara K. (Frontiers in Ophthalmology, 2025)
IntroductionThe eye lens is a sophisticated optical element that provides the eye with both refractive power and transparency as well as the ability to change focus. The latter function diminishes with age as the lens becomes less able to change its shape. The changes with age in lens structure affect its function as a transparent refractive element but much remains misunderstood.MethodsThe review considers the optical parameters of the lens, its gradient of refractive index, and how this may be formed and altered with growth and ageing. The review is structured around three axioms that relate to the creation of the refractive index, the explanation for the lens paradox, and the changes in the structural proteins and how these may be linked to opacification.Results/discussionIt is accepted that the structure/function relationship in the eye lens is explained by the distribution of its proteins forming a gradient of refractive index that provides a high level of image quality to the eye. Delving deeper into explanations for the gradient index creation, the lens paradox and the state of proteins in situ in lenses with cataract, gives reason for doubt. The axioms described indicate which areas require revisiting the literature, reconsideration of accepted thinking, and further experimental investigations.